The impacts of portfolio - based assessment on grade 10 students’ writing performance : - Phạm, Trung Việt (Trường đại học Cần Thơ, 2018)
The current study aims to investigate the impact of portfolio- based assessment on Grade 10 students’ writing performance in a mountainous high school in An Giang province. The study consists of 2 sub purposes (1) examining the impact of portfolio- based assessment on grade 10 students’ writing performance, and (2) examining the impact of portfolio- based assessment on different components of their writing performance.